2018
DOI: 10.3892/ijmm.2018.3435
|View full text |Cite
|
Sign up to set email alerts
|

Renal transplantation increases angiotensin II receptor-mediated vascular contractility associated with changes of epigenetic mechanisms

Abstract: Hypertension is one of the most common complications following renal transplantation, and it increases the risk of graft loss and other cardiovascular diseases. Previous studies have revealed that the use of angiotensin II (Ang II) blockers for preventing and treating hypertension is closely associated with higher survival following renal transplantation. However, the cellular and molecular mechanisms by which the vascular contractility of the recipient is altered in response to Ang II following renal transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…DNA hypermethylation is a hallmark of gene silencing, while DNA hypomethylation promotes active transcription. Recent studies have reported that methylation of Mas1/Agtra1 plays a key role in the regulation of vascular tone [25,26]. For instance, perinatal nicotine exposure enhances vascular contractility that is associated with decreased DNA methylation of Agtra1 in the aorta in adult offspring [27].…”
Section: Discussionmentioning
confidence: 99%
“…DNA hypermethylation is a hallmark of gene silencing, while DNA hypomethylation promotes active transcription. Recent studies have reported that methylation of Mas1/Agtra1 plays a key role in the regulation of vascular tone [25,26]. For instance, perinatal nicotine exposure enhances vascular contractility that is associated with decreased DNA methylation of Agtra1 in the aorta in adult offspring [27].…”
Section: Discussionmentioning
confidence: 99%
“…But all tested antibodies gave signals in tissues from AT1A knock-out mice and nontransfected 4B cells. Despite this first report of aspecificity, the sc-1173 antibodies were still widely used in the literature up to now (Rizzetti et al 2018;Zhao et al 2018;Ribeiro et al 2018) and it has just been discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…Polyclonal antibodies targeting both angiotensin II (AngII) receptors type 1 (AT1) and type 2 (AT2) have been described as non-specific (Benicky et al 2012;Herrera et al 2013;Hafko et al 2013). Despite these findings, antibodies directed against AT1 receptors are still widely used in the literature with more than twenty publications in 2017 using the Santa Cruz aspecific sc-1173 polyclonal antibodies (Chao et al 2017;Young et al 2017;Liu et al 2017) and already five publications in 2018 (Ahad et al 2018;Ishikane et al 2018;Rizzetti et al 2018;Zhao et al 2018;Ribeiro et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In these patients, treatment with angiotensin II (Ang II) blockers for preventing or treating hypertension is closely associated with improved survival. An in vivo study demonstrated that DNA methylation modulated the recipient vascular Ang II receptor (AT1R) gene expression, which in turn increased the vascular contractility in response to Ang II [92]. Another complication in kidney transplant recipients is the new-onset diabetes after transplantation (NODAT), which increases the risk of cardiovascular disease, infections, graft loss, and mortality [93, 94].…”
Section: Dna Methylation In Kidney Transplantationmentioning
confidence: 99%